2021
DOI: 10.1108/bfj-05-2021-0603
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of consumers’ perceived risks in eco-design packaging on food wastage behaviors

Abstract: Purpose Packaging links products to consumers by delivering messages to promote healthy food consumption and reduce wastage. However, studies point to a knowledge gap and skepticism among consumers regarding the impact of eco-design packaging on food wastage reduction. To demystify this skepticism and fill the knowledge gap, this study aims to examine consumers’ perceived risks in eco-design packaging and their impact on consumer food wastage. Design/methodology/ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…The brown stream encloses the human and food industry. According to Zeng (2021), consumers are hindered from using renewable packaging by financial, physical, functional, temporal and social factors in adopting eco‐design packaging. The argument extends the theme towards CE in terms of actual consumption (use) of food and the use of reusable packaging (recovery).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The brown stream encloses the human and food industry. According to Zeng (2021), consumers are hindered from using renewable packaging by financial, physical, functional, temporal and social factors in adopting eco‐design packaging. The argument extends the theme towards CE in terms of actual consumption (use) of food and the use of reusable packaging (recovery).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, consumer sentiment appears crucial in driving towards CE, as consumers can be critical actors in the disposal of organic waste from food consumption (Borrello et al, 2017). Consumer status appears contradictory as consumers may be hindered from using renewable packaging due to financial, physical, functional, temporal and social factors in adopting eco‐design packaging (Zeng, 2021). Therefore, for effective fitting with the CE paradigm, it appears necessary to encourage a change in culture and value perception (Jensen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a lack of consensus in the literature as to whether the environmental attributes of packaging impact consumer purchase decisions [222]. While there may be both positive and negative attributes for sustainable packaging [102], consumers, when purchasing ecodesign packages, may do so for personal benefit considerations rather than social factors, such as protecting the environment [249]. Frequent users of color cosmetics, which could represent more valuable customers, tend to care less about sustainable packaging [35].…”
Section: Economic Sustainabilitymentioning
confidence: 99%
“…In addition, eco-friendly packaging can decrease food waste. Zeng (2021) ship between eco-design, packaging, and food waste from a consumer perspective. It was found that the health consciousness and environmental awareness of consumers with perceived risks regarding eco-design packaging affect food waste decisions.…”
Section: Cluster 3: Eco-friendly Packaging and Consumer Behaviormentioning
confidence: 99%